Integrating social justice into higher education conservation science - Montgomery, RA; Pointer, AM; Jingo, S; Kasozi, H; Ogada, M; Mudumba, T (Oxford University Press, 2022)
Because biodiversity loss has largely been attributed to human actions, people, particularly those in the Global South, are regularly depicted as threats to conservation. This context has facilitated rapid growth in green militarization, with fierce crackdowns against real or perceived environmental offenders. We designed an undergraduate course to assess student perspectives on biodiversity conservation and social justice and positioned those students to contribute to a human heritage-centered conservation (HHCC) initiative situated in Uganda. We evaluated changes in perspectives using pre- and postcourse surveys and reflection instruments. Although the students started the course prioritizing biodiversity conservation, even when it was costly to human well-being, by the end of the course, they were recognizing and remarking on the central importance of social justice within conservation. We present a framework for further integration of HHCC approaches into higher education courses so as to conserve the integrity of coupled human and natural systems globally.